Sensory Characteristics of Fermented Dangke Whey Functional Beverage with Different Levels of Honey Addition - Taufik, Muhammad; Triana, Andi; Rasuli, Nur; Maruddin, Fatma; Kristianti, Novita Dewi; Nawangsari, Dwi Novrina (Jurnal Ilmu-Ilmu Peternakan, 2025)
The characteristics of functional beverages are strongly influenced by the microorganisms used to ferment the lactose contained in whey. In addition, the characteristics of whey functional beverages can also be influenced by the sweetener used. This study aims to determine the panellist acceptance of the sensory characteristics of fermented whey dangke functional beverages with the addition of different levels of honey. The parameters observed in this study were sensory measurements involving panelists, including sensory assessments of the value of taste, sweetness, color, viscosity, and the liking of the panelists for fermented whey products with increasing percentages of honey. The research design used was a complete randomized design. A total of 8, 10, or 12% honey was added, with 5 replications. Significant differences between treatments were followed by Duncan's multiple range test. The results of the analysis of variance revealed that the addition of different honey contents had a significant effect (P<0.01) on the values of sweetness, color, and viscosity. The addition of different concentrations of honey had no significant effect (P>0.01) on flavour value or panellist liking. Increasing the percentage of honey added to fermented whey caused the panelists' assessment of sourness to decrease, whereas the panelists' assessment of sweetness, color, viscosity and favourite increased. The best percentage of honey added was 12%.